Legal Responsibility of Unlabeled Cosmetics Business Actors from the Perspective of Consumer Protection Law - Chrestella Carissa Santoso; Natalis Anggi Saputra; Dominikus Degeda Kola Pati (International Journal of Law, Social Science, and Humanities, 2025)
The circulation of unlabeled cosmetics in Indonesia has become an important issue that threatens the protection of consumer rights. Cosmetics that are not clearly labeled omit crucial and important information for consumers, such as ingredient composition, distribution license, and product expiration date. This risks jeopardizing the health and resulting in financial losses for consumers who are not adequately informed about the products they consume. In this context, the perspective of legal protection of consumers emphasizes that consumers have the right to obtain honest, clear and correct information about the products they buy. According to Law Number 8 Year 1999 on Consumer Protection (UUPK), business actors are required to provide complete and safe information about the products they distribute, in accordance with Article 4 and Article 7 of the UUPK. However, in reality, the circulation of unlabeled cosmetics indicates non-compliance with these provisions, leading to violations of consumer rights. This practice not only harms consumers but also creates legal uncertainty, as it is difficult to claim liability in the event of loss due to the product. Based on the perspective of legal protection of consumers, stricter supervision and strict law enforcement are necessary to ensure that existing regulations are effectively implemented. This aims to protect consumer rights, create legal certainty, and prevent the circulation of unlabeled cosmetics that could potentially harm consumers.